Brazilian Robotics Olympiad: A successful paradigm for science and technology dissemination. (8th September 2016) - Aroca, Rafael V; Pazelli, Tatiana FPAT; Tonidandel, Flavio; Filho, Azamor CA; Simes, Alexandre S; Colombini, Esther L; Burlamaqui, Aquiles MF; Goncalves, Luiz MG
This article introduces the successful methodology adopted for the realization of the Brazilian Robotics Olympiad. Organizational and scientific issues are presented and discussed as well as results of statistical surveys performed with participants that verify the benefits brought by this robotics Olympiad. The Brazilian Robotics Olympiad is a nine-year-old nation-wide initiative created with the mission of promoting robotics among Brazilian students with or without previous knowledge of robotics, fostering their interest to engage in science, technology and engineering studies and careers. The Olympiad is fully free for participants, being annually organized by hundreds of volunteers from several Brazilian universities. It is divided into practical and theoretical components with several levels, each one designed for a certain student age. More than 300, 000 students have already participated in the Brazilian Robotics Olympiad and, according to 58% of these students, the Brazilian Robotics Olympiad helped them to decide which university course to pursue.